Applied corporate finance - Damodaran, Aswath, 1957- (Wiley, 2014)
"Provides finance professionals with practical and succinct advice on how to do corporate finance rather than debate theory, assumptions, or models. Includes applications of corporate finance to real companies. Suitable for MBA program courses on corporate finance and equity valuation"--Resumé vydavatele
Keywords: finance podniku; finanční management; podnikové investice; dividendová politika; business finance; financial management; capital investments; dividend policy; učebnice; případové studie; textbooks; case studies